2016
DOI: 10.2166/wst.2016.034
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the design of rainwater harvesting systems in buildings with green roofs in a Mediterranean climate

Abstract: Green roofs (GRs) are becoming a trend in urban areas, favouring thermal performance of buildings, promoting removal of atmospheric pollutants, and acting as possible water collection spots. Rainwater harvesting systems in buildings can also contribute to the management of stormwater runoff reducing flood peaks. These technologies should be enhanced in Mediterranean countries where water scarcity is increasing and the occurrence of extreme events is becoming very significant, as a result of climate change. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…From the perspective of integrating green roofs with rainwater harvesting systems, previous research has been conducted by the authors and other researchers on a conventional extensive green roof system in Oporto city (Portugal) [35]. This study revealed low runoff coefficient values, but allowed the development of an expression to predict the monthly runoff coefficients for this type of conventional green roof.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…From the perspective of integrating green roofs with rainwater harvesting systems, previous research has been conducted by the authors and other researchers on a conventional extensive green roof system in Oporto city (Portugal) [35]. This study revealed low runoff coefficient values, but allowed the development of an expression to predict the monthly runoff coefficients for this type of conventional green roof.…”
Section: Methodsmentioning
confidence: 96%
“…The pilot green roof was established with three different common aromatic plant species: Satureja montana, Thymus caespititius, and Thymus pseudolanuginosus. Although the pilot system was relatively small (0.70 × 0.70 m 2 ) and could lead to scale distortions in the results, it was thought that these errors would not be significant and that the results met the objective of obtaining a practical mathematical expression that would allow, with acceptable approximation, the determination of average values of the monthly runoff coefficient for a typical extensive green roof [35]. Measurements of the pilot green roof allowed the development of the following expression for monthly runoff coefficient prediction [35]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A construção de telhados verdes, além de auxiliar nas condições térmicas das edificações, pode ser integrada com um sistema de aproveitamento de água pluvial, agindo como um local de coleta de água e removendo poluentes atmosféricos. Com este objetivo, Monteiro et al (2016) Teixeira et al (2017) Os autores apontam que para completo atendimento às normas da ABNT, seria necessário acrescentar um sistema de desinfecção e sugerem que essa necessidade pode inibir os usuários de adquirir um sistema de aproveitamento de água pluvial.…”
Section: Telhado Verdeunclassified